Differential inequalities for hysteresis systems. (1996) - Chernorutskii, Vladimir V.; Krasnosel'skii, Mark A.
Abstract : The theory of differential inequalities is extended to functional-differential equations with hysteresis nonlinearities. A key feature is the existence of a semiorder of the state space of nonlinearity and a special monotonicity of the righthand side of differential inequality. This article is dedicated to the memory of Roland L. Dobrushin.